Secure data sharing scheme supporting efficient synchronous evolution for ciphertext and key - Xincheng YAN; Yue CHEN; Hongyong JIA; Yanru CHEN; Xinyue ZHANG (Tongxin xuebao)
The static property of stored ciphertext in cloud increases the probability that an attacker can crack the ciphertext by obtaining a key,while ciphertext and key updates based on key distribution and re-encryption are excessively expensive.For this problem,a secure data sharing scheme supporting efficient synchronous evolution for ciphertext and key (CKSE-SDS) was proposed.By introducing cryptography accumulator in broadcast encryption,mimicry transformation factor could be constructed supporting time-hopping periodically and efficient synchronous evolution for ciphertext and key could be achieved based on dynamic segmentation and fusion of ciphertext and key,which reduced certainty in the process of encryption and key distribution and increased the difficulty for attackers exploiting security vulnerabilities to obtain key to crack ciphertext as well.Theoretical analysis and security proofs show that the proposed scheme can support secure and efficient data access as well as reduce the probability of a successful attack effectively for an attacker,which can also enhance the system’s active security defense capability.